Penerapan Akad Musyarakah Mutanaqisah dalam Pembiayaan Modal Usaha: Studi di PT. BPRS Metro Madani - Alin Dwi Putri; Suci Hayati; Suraya Murcitaningrum (Economic Reviews Journal, 2026)
This study aims to analyze the implementation of the Musyarakah Mutanaqisah (MMQ) contract in business capital financing at BPRS Metro Madani and to examine customers’ understanding of the partnership and risk-sharing principles embedded in this financing scheme. This research employs a qualitative approach using field research. Data were collected through in-depth interviews and documentation involving bank employees and customers who utilize MMQ financing. The results show that the implementation of MMQ financing at BPRS Metro Madani is conducted through systematic stages, starting from financing application, business feasibility analysis, determination of capital portions and profit-sharing ratios, to the gradual transfer of ownership to the customer. Normatively, the structure of the MMQ contract is consistent with sharia principles as it does not contain elements of riba, provides clear capital contributions, and ensures profit distribution based on mutual agreement between the parties. However, the findings indicate that some customers still have limited understanding of the partnership concept and risk-sharing principles in the MMQ contract, leading them to perceive the financing as a routine installment obligation. In addition, no cases of business loss requiring loss sharing between the bank and customers were found during the period studied, as the bank applies business feasibility analysis and risk mitigation prior to financing approval. This study contributes by highlighting the gap between the theoretical concept of risk sharing in Islamic financing and customers’ understanding in the practical implementation of MMQ financing, emphasizing the importance of strengthening customer literacy regarding partnership-based contracts in Islamic financial institutions.